Islamization of knowledge: challenges and achievements - Moten, Abdul Rashid (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2015)
Islamization of knowledge, though began with the first revelation of the Qur’an, assumed the position of a movement in the 1980s. Since then, scholars have developed models to Islamize knowledge and new institutions have been developed to put these ideas into practice. Based upon documentary evidence and content analysis of the existing literature, this study analyzes the growth and development of this project and measures the achievements in the form of scholarly outputs and man-power development. It is found that the project did make some headway but it failed in many respects. The challenges faced by Muslims in their efforts to Islamize knowledge are numerous and requires concerted effort to make education really Islamic.